Reck and Gpr124 are Essential Receptor Cofactors for Wnt7a/Wnt7b-Specific Signaling in Mammalian CNS Angiogenesis and Blood-Brain Barrier Regulation - Cho, Chris (Neuron, 2017)
Reck, a GPI-anchored membrane protein, and Gpr124, an orphan GPCR, have been implicated in Wnt7a/Wnt7b signaling in the CNS vasculature. We show here that vascular endothelial cell (EC)-specific reduction in Reck impairs CNS angiogenesis and that EC-specific postnatal loss of Reck combined with loss of Norrin impairs blood-brain barrier (BBB) maintenance. The most N-terminal domain of Reck binds to the leucine-rich repeat (LRR) and immunoglobulin (Ig) domains of Gpr124, and weakening this interaction by targeted mutagenesis reduces Reck/Gpr124 stimulation of Wnt7a signaling in cell culture and impairs CNS angiogenesis. Finally, a soluble Gpr124(LRR-Ig) probe binds to cells expressing Frizzled, Wnt7a or Wnt7b, and Reck; and a soluble Reck(CC1–5) probe binds to cells expressing Frizzled, Wnt7a or Wnt7b, and Gpr124. These experiments indicate that Reck and Gpr124 are part of the cell-surface protein complex that transduces Wnt7a- and Wnt7b-specific signals in mammalian CNS ECs to promote angiogenesis and regulate the BBB.